On the Auxiliary Status of Dare in Old English - Tomaszewska, Magdalena (Studia Anglica Posnaniensia, 2015)
OE *durran ‘dare’ belongs to a group of the so-called preterite-present verbs which developed weak past tense forms replacing the originally strong forms throughout the paradigm. The present study hypothesizes that the potential sources of this development are related to the decay of the subjunctive mood in Old English. Further, this corpus-based study analyses the status of DARE in Old English, with the findings showing that the verb displayed both lexical and auxiliary verb characteristics. These results are juxtaposed and compared with the verb's developments in Middle English. The databases examined are the corpus of The Dictionary of Old English in Electronic Form (A-G) and the Innsbruck Computer Archive of Machine-Readable English Texts. In both cases, a search of potential forms was performed on all the files of the corpora, the raw results were then analysed in order to eliminate irrelevant instances (adjectives, nouns, foreign words, etc.). The relevant forms were examined with the aim to check the properties of DARE as a lexical and an auxiliary verb, and compare the findings with Molencki’s (2002, 2005) observations.